Determinan Computer Vision Syndrome (CVS) Pada Karyawan Di Kantor Pengawasan Dan Pelayanan Bea Dan Cukai Tangerang Tahun 2021 - Hutagaol, Riri Grace (2022)
Work using computers by employees absolutely used in the Tangerang Customs and Excise Supervision and Service office. As a result of excessive computer use, Computer Vision Syndrome (CVS) can be a complaint felt by computer user workers. CVS is a complaint in the eye area that occurs due to excessive computer use. The purpose of this study was to know the determinant of CVS in employees at the Tangerang Customs and Excise Supervision and Service Office in 2021. This quantitative analytic study was designed as a cross-sectional study. The sample of this research is employees who work using computers, totaling 80 people with purposive sampling technique. The results of statistical analysis with chi square stated that there was a significant relationship between gender and the use of glasses (p-value=0,042 and p-value=0,013) with CVS, and no significant relationship was found between years of service, age, visibility, and eye rest patterns with CVS (p-value=0,129, p-value=1,000, p-value=0,358 and p-value=0,125). Therefore, computer users must check the condition of the eye for at least 6 months to an optician or eye hospital in order to find out if there are eye refractive errors or other symptoms related to the eye in order to minimize the incidence of CVS.